Development of Electronic Student Worksheet Inquiry-Based with Multiple Representations of Chemistry on Reaction Rate Material to Practice Students Critical Thinking Skills - Rahma, Eka Aprilia; Novita, Dian (Jurnal Pijar Mipa, 2024)
This research aims to describe the feasibility of Electronic Student Worksheet Inquiry with Multiple Chemical Representations to Train Students' Critical Thinking Skills on Reaction Rate Material. The feasibility of e-worksheet is reviewed in terms of validity, practicality, and effectiveness. This research uses the Research and Development (R&D) method with the ADDIE model limited to the development stage. A limited trial was conducted in January 2024 on 32 students who received reaction rate material. The research results showed that the validity of the e-worksheet was declared valid based on the criteria for content validity getting mode four and construct validity getting mode 3. The practicality of e-worksheet was declared practical based on the results of the student response questionnaire, which showed a percentage of 98.4%. e-worksheet was declared effective based on the t-test results with a significance level 0.05, resulting in a t count of 68.50. Based on these results, it can be concluded that e-worksheet is suitable for use in practicing critical thinking skills on reaction rate material.